Thank You to Our Peer Reviewers in 2024 - Enrico Camporeale; Raffaele Marino; Thomas Berger; Yangkang Chen; Doris Folini; Geoffrey Fox; Xiaofeng Li; Donald Lucas; Steve Tobias; Markus Reichstein; John Rundle; Chaopeng Shen; et al. (Journal of Geophysical Research: Machine Learning and Computation)
Abstract On behalf of AGU, the scientific community, and the editorial team of Journal of Geophysical Research: Machine Learning and Computation, we extend our sincere gratitude to the reviewers who dedicated their time and expertise to evaluating manuscripts for us in 2024. Scientific research can now be communicated in various ways, yet peer review remains the cornerstone of scholarly publishing. We deeply appreciate the reviewers who devoted hours to reading and providing insightful feedback. The high quality of our published papers is a testament to their commitment to this vital community service.